الاغتراب النفسي في الشعر الليبي المعاصر ديوان "أنين الجذوع" ل : سعيد الفاندي أنموذجا - انتيرة, كريمة الهادي (Al-Qurtas, 2026)
الاغتراب النفسي في الشعر الليبي المعاصر ديوان "أنين الجذوع" ل : سعيد الفاندي أنموذجا